2018
DOI: 10.15560/14.1.167
|View full text |Cite
|
Sign up to set email alerts
|

First record of Molossops neglectus Williams & Genoways, 1980 (Chiroptera, Molossidae) from the state of Santa Catarina, southern Brazil

Abstract: Herein we describe the first records of Molossops neglectus for the state of Santa Catarina, Brazil. The records are based on 3 specimens captured in the municipalities of Chapecó and São Domingos, in the western portion of the state. Considering that M. neglectus is an infrequent species in field surveys, new data on its geographical range is important to better understand the biology and ecology of M. neglectus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In Santa Catarina, Molossidae has 10 species recorded (Passos et al, 2010;Carvalho et al, 2017;Althoff et al, 2018), which includes the specie M. molossus, evaluated in the present study. These bats are medium size insectivores characterized by present rounded ears and close to the midline above the head, hair dark brown to reddish brown and a ventral tuft of hair on the upper lip (Weber et al, 2013;Reis et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Santa Catarina, Molossidae has 10 species recorded (Passos et al, 2010;Carvalho et al, 2017;Althoff et al, 2018), which includes the specie M. molossus, evaluated in the present study. These bats are medium size insectivores characterized by present rounded ears and close to the midline above the head, hair dark brown to reddish brown and a ventral tuft of hair on the upper lip (Weber et al, 2013;Reis et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…Bats are important in natural environment due to their high food plasticity, as insect species controllers, pollinators and dispersers (Fleming et al, 1972), interacting with numerous environmental elements (Bernard and Fenton, 2007) and still has an important role in ecosystem dynamics (Kalko, 1998;Bernard, 2001). Currently, about 1,384 species have been described worldwide (Taylor and Tuttle, 2019), of which 182 species found in Brazil (Nogueira et al, 2018), and at least 50 species with confirmed records in Santa Catarina state (Passos et al, 2010;Carvalho and Fabián, 2011;Cherem and Althoff, 2015;Carvalho et al, 2017;Althoff et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento sobre a distribuição e a história natural dos mamíferos de Santa Catarina vem aumentando desde as primeiras listas compilando as espécies documentadas para o estado (CIMARDI, 1996;CHEREM et al, 2004). Estudos conduzidos em diversas regiões do estado têm reportado uma mastofauna diversificada, atualmente estimada em 175 espécies, 144 das quais se referem a mamíferos terrestres (CHEREM et al, 2004;PASSOS et al, 2010;CARVALHO & FÁBIAN, 2011;REIS et al, 2011;DIAS et al, 2016;ALTHOFF et al, 2017ALTHOFF et al, , 2018CARVALHO et al, 2017;FEIJÓ et al, 2018;OLIVEIRA et al, 2021).…”
Section: Introductionunclassified